Characterization of Thelenota ananas and Its Potential as a Natural Source of Antioxidants - Budiarso, Fona; Sorisi, Angle; Fatimawali, Fatimawali (Universitas Sam Ratulangi, 2026)
The sea cucumber Thelenota ananas, commonly found in tropical waters, possesses significant biological potential. This study aims to assess the antioxidant potential of Thelenota ananas extract obtained from the Manado sea. The simplicia was analyzed for organoleptic properties, moisture content (9.8%), and ash content (23%). Bioactive compounds were identified through color and foam reactions, while antioxidant activity was measured using the DPPH method. The extract was found to contain saponins, terpenoids, and alkaloids. The antioxidant activity of the extract, with an IC50 value of 99.8 ppm, demonstrates strong antioxidant properties, though less potent than the control, vitamin C (IC50 of 45.5 ppm). These findings suggest that while Thelenota ananas extract exhibits substantial antioxidant activity, it is still less effective than vitamin C. This research highlights the potential of Thelenota ananas as a natural antioxidant source for the development of health products.